Determinar o valor de "x" na equação:
5^(x+1) + 5^x + 5^(x-1)=775
Soluções para a tarefa
Respondido por
62
Você tem que saber que:
a^(b+c) = a^b * a^c
a^(b-c) = a^b / a^c
a^b = a^c ====> b =c
Então, vamos lá:
5^(x+1) + 5^x + 5^(x-1) = 775
5^x * 5^1 + 5^x + 5^x * 5^-1 = 775
5^x (5 + 1 + 1/5 = 5² * 31
5^x(31/5) = 5² * 31
5^x(1/5) = 5²
5^(x-1) = 5²
x - 1 = 2
x = 3
a^(b+c) = a^b * a^c
a^(b-c) = a^b / a^c
a^b = a^c ====> b =c
Então, vamos lá:
5^(x+1) + 5^x + 5^(x-1) = 775
5^x * 5^1 + 5^x + 5^x * 5^-1 = 775
5^x (5 + 1 + 1/5 = 5² * 31
5^x(31/5) = 5² * 31
5^x(1/5) = 5²
5^(x-1) = 5²
x - 1 = 2
x = 3
lizVasquez:
obrigado :)
Perguntas interessantes
História,
1 ano atrás
Português,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Química,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás